Water quality monitoring system approach to support Guapi-Macacu River basin management, Rio de Janeiro, Brazil. - AKÉ HERNÁNDEZ, J. H. (2010)
Scarcity of surface water and groundwater has initiated actions in water quality management to prevent and reduce the negative impacts on water sources for human consumption and ecological performance. Decentralized Water policy establishes the framework to have maximum use with a proper management of the resource with public participation at the river basin. Water quality monitoring is an essential component of water resource management, providing water quality and quantity information to organizations for decision making. In 1997, Brazil approved such water policy, National Water Resource Policy (NWRP), consisting with guided actions and instruments to establish integrated water resource management with federal, state and local support. In 2001, the National Water Agency (ANA) was established to implement the water policy and prevent river water pollution. In transitional and developing countries, this type of water policy is modern and ambitious, consisting of limiting factors that hinders with providing water quality data at the river basin, hence providing limited information for decision making. For further enhancement on water monitoring, the availability and collection of adequate water quality information is needed. The Guapi-Macacu River Basin (GMRB), located in north-eastern region of Guanabara Bay Basin in the federal state of Rio de Janeiro, consist of protected areas, good water quality and quantity in the upper reaches of the basin and in the head waters of Guapiaçu and Macacu rivers. The general objective of the master´s thesis was to analyse the current water quality monitoring system to contribute for the Guapi-Macacu river basin management plan. The methodology used was a combination of two conceptual approaches: Driving Force-Pressure-State-Impact-Response (DPSIR) Framework and Strategic Environmental Analysis (SEAN). ANA maintains a national hydro-meteorological network for water quantity and quality coordinated with state water monitoring agencies and provides the collected information to water management departments via various websites links to the database. In Rio de Janeiro, the State Institute of Environment (INEA), does water quality monitoring within its environmental monitoring system to supervise the commitment of industries to prevent environmental pollution in the river basins. The Guanabara Bay Basin Committee (GBBC) is the public participatory body in the management, coordinating and planning of water resources with governmental bodies under the State Secretary of Environment. It was observed that at the river basin, three entities conduct water quality monitoring, INEA, CEDAE (State Water and Sewage Company) and AMAE (Municipal Water and Sewage Authority), with the variation of parameters, frequencies and sampling sites mostly based on three national Norms, Resolutions CONAMA # 247/2000, CONAMA # 357/2005 and Ordinance #518/2004. Recently, GMRB, with land use changes, mainly to farming activities, along with increase number of industrial establishments and untreated domestic sewage production, the current sampling sites of both monitoring entities are irrelevant in collecting representative water quality data to comply with control of environmental pollution. Based on the results of this research, recommendations were given for the newly established management plan of the environmental protected area of the basin of Macacu river in GMRB.